Caesarean section and the association with migraine: a retrospective register-linked HUNT population cohort study. Issue 11 (18th November 2020) - Kristoffersen, Espen Saxhaug; Børte, Sigrid; Hagen, Knut; Zwart, John-Anker; Winsvold, Bendik Slagsvold
Abstract : Objectives: To evaluate the association between caesarean section and migraine in a population-based register-linked cohort study. Setting: Data from the population-based Nord-Trøndelag Health Studies (HUNT2 and HUNT3) were linked to information from the Norwegian Medical Birth Registry. Participants: 65 343 participants responded to the headache questions in any of the two HUNT studies. Only those answering the headache questions in HUNT2 or 3 and had information about mode of delivery in the Norwegian Medical Birth Registry (born after 1967) were included. Our final sample consisted of 6592 women and 4602 men, aged 19–41 years. Outcomes: ORs for migraine given caesarean section. Analyses were performed in multivariate logistic regression models. Results: After adjusting for sex, age and fetal growth restriction, delivery by caesarean section was not associated with migraine later in life (OR 0.86, 95% CI 0.64 to 1.15). Delivery by caesarean section was associated with a reduced OR of non-migrainous headache (OR 0.77, 95% CI 0.60 to 0.99). Conclusion: No association was found between caesarean section and migraine in this population-based register-linked study.